Innovative Learning Media Exhibition: Cultivating Motivation among Islamic Education Students to Create Engaging Learning Media - Umi Hijriyah; Baharudin Baharudin; Ida Fiteriani; Fitriati Fitriati; Nurul Azizah (EDUKASIA, 2024)
This research aimed to determine the relationship between media exhibitions and students' motivation. It was based on the fact that PAI students got lack motivation to create innovative learning media. This lack of motivation was caused by a limited understanding of the importance of learning media, insufficient skills and creativity, and inadequate facilities. The research design employed in this study was quantitative with a correlational approach. The sample consisted of 60 students from the fifth semester of the PAI program, class of 2022, at UIN Raden Intan Lampung. The instrument used in this study was a non-test instrument in the form of a questionnaire. The results from the T-test and correlation test revealed a significant relationship between media exhibitions and the motivation of students in the Islamic Religious Education program. The implication of this research was that it could serve a reference for taking further actions to address issues related to media exhibitions and students' motivation to develop or create innovative learning media. This study was expected to be used by educators as a reference for understanding the relationship between media exhibitions and the motivation of PAI students to create engaging learning media.